Push–pull ruthenium diacetylide complexes: new dyes for p-type dye-sensitized solar cells. Issue 24 (17th February 2016) - Lyu, Siliu; Farré, Yoann; Ducasse, Laurent; Pellegrin, Yann; Toupance, Thierry; Olivier, Céline; Odobel, Fabrice
Abstract : A couple of novel donor–π–acceptor dyes based on organometallic ruthenium diacetylide complexes (SL1 andSL2 ) have been designed and synthesized for use in NiO-based p-type dye-sensitized solar cells (p-DSCs). Abstract : A couple of novel donor–π–acceptor dyes based on organometallic ruthenium diacetylide complexes (SL1 andSL2 ) have been designed and synthesized for use in NiO-based p-type dye-sensitized solar cells (p-DSCs). The optical and electrochemical properties of the dyes were assessed and theoretical calculations were performed to rationalize the experimental data. The best performing dye in NiO-based p-DSC devices is the red dyeSL1, which gives a photocurrent density of 2.25 mA cm −2 and maximum IPCE of 18%. This represents a promising result, paving the way for future finely tuned organometallic efficient dyes for such application.